A highly directional eight‐hole coupling circular waveguide coupler. Issue 8 (26th April 2022) - Ma, Jia; Zhong, Weiye; Zhang, Hui; Zhang, Chao; Xu, Zhiqiang; Sun, Zhijie; Chen, Dong; Liu, Qinghui; Shen, Zhiqiang
Abstract: Aiming at the system noise temperature calibration of the K‐band seven‐beam cryogenic receiver on Tianma Radio Telescope, a design of K‐band highly directional coupler is proposed in this paper. Based on the hole coupling principle proposed by Gian Guido Gentili, an eight‐hole coupling circular waveguide directional coupler is designed by ANSYS HFSS software. Through the distribution mode of eight coupling holes, the excellent performance and compact structure have been realized. Measurement shows that the reflection coefficient is less than −25 dB, coupling degree is stable within −25 ± 1 dB, isolation degree is lower than −35 dB, and directivity coefficient is greater than 10 dB in its operating frequency range.